Environmental Regulation of PndbA600, an Auto-Inducible Promoter for Two-Stage Industrial Biotechnology in Cyanobacteria - Madsen, Mary Ann; Hamilton, Graham; Herzyk, Pawel; Amtmann, Anna (Frontiers in Bioengineering and Biotechnology, 2021)
Cyanobacteria are photosynthetic prokaryotes being developed as sustainable platforms that use renewable inputs (light, water and air) for diverse applications in energy, food, environment and medicine. Despite the attractive promise cyanobacteria offer industrial biotechnology, slow growth rates pose a major challenge in processes which typically require large amounts of biomass and are often toxic to the cells. Two-stage cultivation strategies are an attractive solution to prevent any undesired growth inhibition by de-coupling biomass accumulation (stage I) and the industrial process (stage II). In cyanobacteria, two-stage strategies involve costly transfer methods between stages I and II and little work has focused on using the distinct growth and stationary phases of batch cultures to auto-regulate stage transition. In this work, we identified and characterised a growth phase-specific promoter, which can serve as an auto-inducible switch to regulate two-stage bioprocesses in cyanobacteria. First, growth phase-specific genes were identified from a new RNAseq dataset comparing two growth phases and six nutrient conditions in Synechocystis sp. PCC 6803 including two new transcriptomes for low Mg and low K. A type II NADH dehydrogenase (ndbA) showed robust induction when the cultures transitioned from exponential to stationary growth. Behaviour of a 600-bp promoter sequence (PndbA) was then characterised in detail following expression of PndbA:GFP in Synechococcus sp. PCC 7002. Culture density and growth media analyses showed that PndbA activation was not dependent on increases in culture density per se, but on N availability and another activating factor present in the spent media of stationary phase cultures (Factor X). PndbA deactivation was dependent on changes in culture density and either N availability or Factor X. Electron transport inhibition studies revealed a photosynthesis-specific enhancement of active PndbA levels. Our findings are summarised in a model describing the environmental regulation of PndbA which can now inform the rational design of two-stage industrial processes in cyanobacteria.